2019
DOI: 10.2147/rmhp.s228659
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trend Analysis And Seasonality Of Tuberculosis Among Patients At The Hiwot Fana Specialized University Hospital, Eastern Ethiopia: A Retrospective Study</p>

Abstract: PurposeTuberculosis (TB) is one of the top 10 leading killer diseases in developing countries, particularly in Sub-Saharan Africa, including Ethiopia. Thus, this study aimed to assess the trend analysis and seasonality of TB at Hiwot Fana Specialized University Hospital, Eastern Ethiopia.Methods and patientsA hospital-based retrospective study was conducted on 8,001 patients by reviewing all available patients’ data from January 1, 2015 to April 30, 2019, at the Hiwot Fana Specialized University Hospital, East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“… 19 In contrast to this, the current study was less than as compared to the previous studies reported in Nepal (13.8%), 20 Zimbabwe (11%), 21 and Ethiopia: Metehara sugar factory (14.2%). 22 Western Oromia (21.3%), 23 Addis Ababa (15.11%), 24 Gambella regional state (20.0%), 25 Dubti Hospital in Afar region (24.5%), 26 Western Oromia (21.3%), 27 at University of Gondar (24.6%), 16 Debre Markos Referral Hospital (23.2%), 28 Hiwot fana Hospital Harar (15.7%), 29 and Djibouti Hospital (24.5%). 26 The variations may be due to geographical variation, climatic condition and diagnostic methodology.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In contrast to this, the current study was less than as compared to the previous studies reported in Nepal (13.8%), 20 Zimbabwe (11%), 21 and Ethiopia: Metehara sugar factory (14.2%). 22 Western Oromia (21.3%), 23 Addis Ababa (15.11%), 24 Gambella regional state (20.0%), 25 Dubti Hospital in Afar region (24.5%), 26 Western Oromia (21.3%), 27 at University of Gondar (24.6%), 16 Debre Markos Referral Hospital (23.2%), 28 Hiwot fana Hospital Harar (15.7%), 29 and Djibouti Hospital (24.5%). 26 The variations may be due to geographical variation, climatic condition and diagnostic methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous TB trend analysis held in the Tigray Region, [ 11 , 12 ] Bale Zone of Oromia Region, [ 13 ] East Gojjam Zone of Amhara Region, [ 14 ] Addis Ababa, [ 15 ] Harari Region, [ 16 ] and Awi Zone of Northwest Amhara Region [ 17 ] reported a decreasing trend of TB over time. Our finding also shows a decreasing trend of the disease though it lacks consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding also shows a decreasing trend of the disease though it lacks consistency. Previous reports in the Harari Region [ 16 ] and some parts of the Amhara and Oromia Regions [ 18 ] reported seasonal variations in TB incidence. [ 16 ] Differences in comorbid diseases, the population’s knowledge about TB, institutional capacity for diagnosis of TB, and strategic approaches in the prevention of TB may contribute to variations in TB patterns and disease burden among these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study further reveal that TB infections among children tended to exhibit a seasonal pattern with 3 peaks experienced in March, June and September respectively. Despite very few studies highlighting the importance of seasonal variations coinciding with TB infections, seasonality of TB infections has been documented in other studies PLOS DIGITAL HEALTH [68,69,70]. While other studies did not directly attribute TB infections to seasonal patterns, Jaganath et al [71] found a link between the peaks of the rain and influenza seasons and increased TB infections among children in Uganda.…”
Section: Discussionmentioning
confidence: 99%